Dinamika Dispensasi Nikah Dibawah Umur di Pengadilan Agama Pasca Disahkan UU. 16 Tahun 2019 (Studi Kasus Pengadilan Agama Kab. Bulukumba) - Amri, Muh. Zul Atsari; Syarifuddin Abu Baedah, Said; Arsyad, Yusri Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the dynamics of underage marriage dispensation at the Religious Court of Bulukumba Regency following the enactment of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage. This law stipulates that the minimum age for marriage is 19 years for both males and females. However, underage marriages continue to occur due to various reasons, particularly out-of-wedlock pregnancies and strong local cultural pressures. This research uses a qualitative descriptive approach, employing data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the number of marriage dispensation requests at the Bulukumba Religious Court fluctuated significantly after the enforcement of Law No. 16 of 2019. In 2019, there were 102 applications, which sharply increased to 206 in 2020, and then gradually decreased in subsequent years. However, this decline in applications does not necessarily indicate a decrease in actual child marriage practices. Many underage marriages occur informally and are not legally registered, such as unregistered (siri) marriages. This reveals a gap between official legal data and social realities.